The Bay’at Ar-Ridwan and Allah's Reward for the Muslims : (Analysis of the Tafsir of Surah Al-Fatḥ Verses 18-19) - Ammar; Kharis Nugroho (Lembaga Penelitian, Penerbitan dan Pengabdian kepada Masyarakat (LP3M) IAIFA Kediri, 2025)
The Bay’at Ar-Ridwan is an important event in Islamic history that illustrates the commitment and loyalty of the Muslims to the Prophet Muhammad, which took place under a tree in Hudaybiyyah. This event not only became a symbol of unity and determination but also a moment when Allah granted a great reward to the Muslims, as explained in Surah Al-Fatḥ. The purpose of this research is to analyze how the bay’at Ar-Ridwan and Allah's response to the Muslims are explained in the interpretation of Surah Al-Fatḥ, particularly in the context of verses related to the promise of victory and divine assistance. This research uses classical and contemporary exegesis approaches to explore the historical and spiritual context of the bay’at Ar-Ridwan event and the implications of Allah's response in the lives of Muslims. The research results show that Surah Al-Fatḥ verses 18 to 19, illustrate how the loyalty of Muslims in the bay’at Ridwan brings about Allah's pleasure and assistance, which is evident in their future victories, including the Treaty of Hudaybiyyah that paved the way for the spread of Islam.